2015
DOI: 10.1039/c5ob00688k
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel isatin-based sulfonamides with potent and selective inhibition of the tumor-associated carbonic anhydrase isoforms IX and XII

Abstract: A series of 2/3/4-[(2-oxo-1,2-dihydro-3H-indol-3-ylidene)amino]benzenesulfonamides, obtained from substituted isatins and 2-, 3- or 4-aminobenzenesulfonamide, showed low nanomolar inhibitory activity against the tumor associated carbonic anhydrase (CA, EC 4.2.1.1) isoforms IX and XII - recently validated antitumor drug targets, being much less effective as inhibitors of the off-target cytosolic isoforms CA I and II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…The Schiff base VI showed a potent inhibitory activity against hCA IX (Ki ¼ 1.1 nM) and had a high selectivity for isoform hCA IX compared to the cytosolic isozymes hCA I and hCA II [23] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The Schiff base VI showed a potent inhibitory activity against hCA IX (Ki ¼ 1.1 nM) and had a high selectivity for isoform hCA IX compared to the cytosolic isozymes hCA I and hCA II [23] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the main problem with the drug design of CA IX inhibitors was to obtain compounds which should selectively inhibit CA IX without a significant inhibitory effect against the physiologically dominant, highly abundant isoforms CA I and II (and also other off‐target isoforms) . This goal seemed to be difficult to achieve initially, but several classes of sulfonamides and their isosteres (sulfamates, sulfamides), most of which were obtained using the tail approach, allowed to obtain compounds with these features . Only the most relevant studies will be mentioned here, as this class of CAIs is the most investigated one and a high number of drug design studies (>400) have been reported since 2003 .…”
Section: Development Of Agents Targeting Carbonic Anhydrase IXmentioning
confidence: 99%
“…Thus, these three subclasses of CAIs will be dealt with together here in this section. All these studies allowed the detailed understanding of the factors governing activity and selectivity for inhibiting CA IX over other CA isoforms, and are summarized below: the zinc‐binding group of the sulfonamide, sulfamate, and sulfamide is not highly influential for obtaining potent and CA IX‐selective inhibitors. In fact, many classes of such derivatives show similar CA IX inhibitory/selectivity profiles, such as various sulfonamides, sulfamates, and sulfamides …”
Section: Development Of Agents Targeting Carbonic Anhydrase IXmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, they have also been reported to possess various types of biological properties such as anticancer [17], antibacterial [18], antimicrobial [19,20], antimalarial [21], antihypertensive [22], antitumor [23], and antiinflammatory activities [24][25][26][27][28][29][30][31], among others. Among these, the anticancer activity was found to take place through a variety of mechanisms such as disruption of the microtubule assembly, cell cycle arrest in the G1 phase, functional suppression of the transcriptional activator NF-Y, angiogenesis and carbonic anhydrase inhibition [15,16].…”
Section: Introductionmentioning
confidence: 99%